Understanding, Sanctions, and Tax Awareness of Taxpayer Compliance with Information Systems as Moderation Variables - Seftiannoor, Aulia; Syahdan, Saifhul Anuar; Ruwanti, Gemi; Boedi, Soelistijono (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to obtain empirical evidence of the influence of understanding, sanctions and tax awareness with information systems as moderating variables. The population in this study is café MSMEs registered with the Ministry of Cooperatives and SMEs as many as 61 businesses. The sampling technique used saturated sampling. The number of samples obtained was 32 respondents. The data analysis technique used is multiple linear regression. The results showed that tax awareness had a positive and significant effect on taxpayer compliance, while tax understanding and tax sanctions had no effect on taxpayer compliance. Information systems moderate the effect of tax understanding, tax sanctions and tax awareness on taxpayer compliance.